Sports-related injuries and illnesses in Paralympic athletes - Fagher, K. (British Journal of Sports Medicine, 2021)
The aim of the thesis was to gain an in-depth understanding of the epidemiology and data collectionmethods of sports injuries and illnesses in Paralympic sport to assist the development of evidence- based preventive measures. To do this, the author combined holistic approaches including athletes` voices with empirical and systematic ones.